When Co10mbian Journa1ists took to the streets - Vallejo, Maryluz; Revista Directo Bogotá (Pontificia Universidad Javeriana - Facultad de Comunicación y Lenguaje, 2006)
Here we attempt to trace [he origios and evolution of two main news genres. i.e., the news srory and the interview. at the outset of journalistic modernity in Colombia in the late 19th century, staked out and pulled by technological developments (and even wars), from which the first reporters and correspondents emerged. The first news agencies ccopped up too in the midst of this confrontational scenario atodds with the model of objectivity championed by AngloSaxon journalism.